2022
DOI: 10.5194/acp-22-65-2022
|View full text |Cite
|
Sign up to set email alerts
|

New investigations on homogeneous ice nucleation: the effects of water activity and water saturation formulations

Abstract: Abstract. Laboratory measurements at the AIDA cloud chamber and airborne in situ observations suggest that the homogeneous freezing thresholds at low temperatures are possibly higher than expected from the so-called “Koop line”. This finding is of importance, because the ice onset relative humidity affects the cirrus cloud coverage and, at the very low temperatures of the tropical tropopause layer, together with the number of ice crystals also the transport of water vapor into the stratosphere. Both the appear… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…4). The decrease starts at 2230 LT at the 3-m level, a half-hour later at 18-m and 2 hours later at 42-m. At 3-m, RHl and RHi are too low for aerosol deliquescence and solution droplet freezing to occur (Baumgartner et al, 2022). Note that we also ensured that the station exhausts do not affect our measurements (see grey shading in Fig.…”
Section: Back-trajectory Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…4). The decrease starts at 2230 LT at the 3-m level, a half-hour later at 18-m and 2 hours later at 42-m. At 3-m, RHl and RHi are too low for aerosol deliquescence and solution droplet freezing to occur (Baumgartner et al, 2022). Note that we also ensured that the station exhausts do not affect our measurements (see grey shading in Fig.…”
Section: Back-trajectory Analysismentioning
confidence: 99%
“…In this particular case, ice crystals may form through freezing of solution aerosol particles also named haze droplets (Heymsfield and Sabin, 1989;Girard and Blanchet, 2001) when the relative humidity reaches a value that depends on the particle size and water activity. This value is above the saturation with respect to ice -so the air is supersaturated with respect to ice -but is lower than the liquid water saturation (Koop et al, 2000;Baumgartner et al, 2022). There is also evidence that solution aerosol particles can also freeze heterogeneously due to the presence of INPs (DeMott et al, 1998;Kärcher and Lohmann, 2003) but this process remains poorly understood especially at very low temperatures (Heymsfield et al, 2017).…”
mentioning
confidence: 99%
“…Nevertheless, if the instrument is embedded in a foggy air, some ice particles may enter from below due to turbulent eddies and the mechanical aspiration. We have therefore analytically estimated the effect of sublimation of thin-fog ice particles -with a typical size of about 10 µm (Santachiara et al, 2016) and a typical number concentration of 0.5 cm −3 (Baumgartner et al, 2022) -on the RHl measurements (not shown). The obtained RHl change values are of the order of a few percentage points at most depending on the ice crystal shape assumption, on the ambient temperature and relative humidity values, and on the fraction of particles that sublimate.…”
Section: Humidity Measurementsmentioning
confidence: 99%
“…The exact value of the threshold also depends on the size of the particle, as well as on the composition thereof and on the formulation and uncertainties of water activities and saturation vapour pressure. Individually, those effects make RHi T vary by about 1 % to 5 % (see Baumgartner et al, 2022). An envelop of 5 % has therefore been added around the Koop's curve in our graphs.…”
Section: Humidity Measurementsmentioning
confidence: 99%
See 1 more Smart Citation